2016
DOI: 10.1002/mren201500074
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Methyl Methacrylate Atom Transfer Radical Suspension Polymerization Process: Polymerization and Particle Kinetics

Abstract: increase in viscosity), [15] suspension polymerization is one of the most important technologies applied in the poly merization industry. A key consideration in designing a suspension polymerization is to achieve such that desired molecular microstructure and droplet/particle size dis tribution (PSD) of polymers are satisfied. The number average molecular weight (M n ) and polydispersity index (PDI), as the most basic performance indices of polymer affecting the polymer enduse properties, are mainly determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Notably, computer simulations represent a powerful strategy to deal with limitations of the experimental characterization of polymer layers and polymers in general, including the quantification of the temporal evolution of average chain-length characteristics, monomer sequences, and the composition of polymer chains. Several modeling techniques have been developed to study the kinetics of homogeneous polymerizations in general, distinguishing between deterministic and stochastic approaches. In SIP, one typically focuses on only two of them, namely, the deterministic method of moments (MoM), which relies on solving a set of ordinary differential equations to calculate the change of the monomer conversion and average polymerization characteristics, and the Monte Carlo (MC) method, as based on the consecutive sampling of reaction events or mass transfers (species movements) according to discrete reaction probabilities. , For example, Zhu et al used MoM to study SI-CRP from flat solid surfaces and focused on the simulation of the temporal variation of monomer conversion, polymer-layer thickness, number-average molar mass, and dispersity in both phases. Assuming ballpark values for the rate coefficients involved, these authors found that the surface-tethered polymer chains displayed less controlled average molecular characteristics compared to those formed in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, computer simulations represent a powerful strategy to deal with limitations of the experimental characterization of polymer layers and polymers in general, including the quantification of the temporal evolution of average chain-length characteristics, monomer sequences, and the composition of polymer chains. Several modeling techniques have been developed to study the kinetics of homogeneous polymerizations in general, distinguishing between deterministic and stochastic approaches. In SIP, one typically focuses on only two of them, namely, the deterministic method of moments (MoM), which relies on solving a set of ordinary differential equations to calculate the change of the monomer conversion and average polymerization characteristics, and the Monte Carlo (MC) method, as based on the consecutive sampling of reaction events or mass transfers (species movements) according to discrete reaction probabilities. , For example, Zhu et al used MoM to study SI-CRP from flat solid surfaces and focused on the simulation of the temporal variation of monomer conversion, polymer-layer thickness, number-average molar mass, and dispersity in both phases. Assuming ballpark values for the rate coefficients involved, these authors found that the surface-tethered polymer chains displayed less controlled average molecular characteristics compared to those formed in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, given that the effect of polymerization was ignored, the complete flow fields in suspension polymerization reactors remained unclear. Recently, our group numerically simulated the multiphase flow characteristics and multiscale properties in various polymerization reactors. Specifically, we built a coupled model comprising the CFD model, PBM, and polymerization moment equations. , However, we mostly focused on the macroscale gas–solid flow field instead of the liquid–liquid system. Wang et al , conducted several simulations to study the dynamic behavior of the atom transfer radical copolymerization (ATRcoP) in a continuous stirred-tank reactor (CSTR).…”
Section: Introductionmentioning
confidence: 99%
“…However, they only considered ideal reactors. Although previous studies have proposed a comprehensive model to simulate the batch suspension ATRP of MMA while considering the polymerization and particle dynamics, this model ignores the flow fields …”
Section: Introductionmentioning
confidence: 99%